ETIKA RELIGIUS DALAM TRADISI RITUAL MAPAG TOYA - Desak Putu Rai Vitri Suastiki (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The purpose of this research is to conduct a study of religious ethics implemented in the ritual tradition of mapag toya by the Hindu community in Pelapuan Village, Busungbiu Subdistrict, Buleleng Regency, Bali. This research is designed in an interpretive descriptive type in an effort to find answers to the three problem formulations, namely how is the implementation, what is the function, and how is the content of religious ethical values in the mapag toya tradition? This study produced three findings related to religious ethics in the implementation of the mapag toya ritual in the Hindu community in Pelapuan Village,. First, the implementation of the mapag toya ritual involves the procedures for carrying out the ceremony in sequences that comply with the stages that show the systematics of Hindu religious ceremonies. Second, the function of carrying out the mapag toya ceremony is to request the irrigation system, raise awareness of Hindus in carrying out yadnya before Ida Sang Hyang Widhi Wasa, and increase sradha (belief) and bhakti (devotion) of Hindus to Ida Sang Hyang Widhi Wasa because with Thus, Hindus in the current era of globalization can still live up to religious teachings in the midst of the swift influence of modernization. Third, religious ethical values in the mapag toya ceremony are a moral order in which humans are given the opportunity to do good and to harmonize individual desires, emotions and desires that are directed towards a better life. In this regard, in relation to the philosophical dimension, religious ethics in the mapag toya tradition shows the existence of moral principles that guide Hindus in their behavior towards improving the quality of life.